Study on the expression of vacuolar proton PUMP ATPase subunit F that contributes in abiotic stress tolerance of Jute (corchorus olitorious) - Rahman, Ahasanur (BRAC University, 2011)
This thesis is submitted in a partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2011